176k views
5 votes
A student is trying to solve the system of two equations given below: Equation P: y + z = 6 Equation Q: 3y + 4z = 1 Which of these is a possible step used in eliminating the y-term?

(y + z = 6) ⋅ 4
(3y + 4z = 1) ⋅ 4
(y + z = 6) ⋅ −3
(3y + 4z = 1) ⋅ 3

User Galled
by
5.8k points

2 Answers

6 votes
c is the answer since you are trying to make the ys number (-/+) of the value the other y contains
(3) so you will multiply the first equation by -3 to be able to eliminate y
User Hcarver
by
6.2k points
3 votes

Answer:

Option C is correct

(y + z = 6) ⋅ −3

Explanation:

As per the statement:

A student is trying to solve the system of two equations given below:

Equation P: y + z = 6 ....[1]

Equation Q: 3y + 4z = 1 ....[2]

Multiply the equation [1] by -3 to both sides we have;


-3 \cdot (y+z = 6)

or


-3y -3z = -18 ......[3]

Add equation [2] and [3] to eliminate the y-term;


z = -17

or

z = -17

Therefore, the possible step used in eliminating the y-term is, (y + z = 6) ⋅ −3

User LaaasBIGL
by
6.3k points